Thermal sensation after open water swimming depends on skin cool sensitivity rather than core temperature - Fujimoto, T.; Matsuura, Y.; Baba, Y.; Hara, R. (XIVth International Symposium on Biomechanics and Medicine in Swimming Proceedings, 2023)
INTRODUCTION In open water swimming (OWS) races take place in lower water temperatures (Tw ), swimmers often drop out due to severe cold sensation and/or hypothermia (Brannigan et al., 2009). Although changes in core and skin temperatures during OWS are assumed to vary across swimmers, it is unclear what influences individual differences in whole-body thermal sensation (TS) among OWS swimmers. The present study examined the relationships between whole-body TS and core temperature (Tcore ) during OWS, and skin cool sensitivity.